Peran DP3APM Kota Medan Terhadap Anak Korban Kekerasan Seksual; Analisis Fiqh Siyasah dan Pidana Islam - Sidik, M. Nurhadi; Yamamah, Ansari (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
Handling cases of sexual violence against children is a critical issue within the context of child protection and social justice. This study aims to analyze the role of the Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DP3APM) of Medan City in addressing cases of sexual violence against children using an approach based on fiqh syiasah and Islamic criminal law. The study examines how DP3APM Medan implements policies and programs to protect children who are victims of sexual violence and how these policies align with the principles of fiqh syiasah and Islamic criminal law. This article is classified as field research based on qualitative methods. The methodology used includes empirical legal studies and normative legal analysis. The research findings indicate that DP3APM Medan plays a crucial role in protecting child victims of sexual violence and strives to align its policies with the principles of fiqh syiasah and Islamic criminal law. However, to enhance the effectiveness of protection and law enforcement, further efforts are needed to address existing challenges and ensure more comprehensive and Islamically aligned policy implementation.